The Use Of Specific Expertise While Research On Documents Made In The Form Of Plastic Cards - Sezonov, Viktor (Archives of Criminology and Forensic Sciences, 2023)
Abstract. The article highlights issues related to the rising circulation of documents made on the basis of plastic cards in Ukraine and the increase in offenses involving their use. Timely application of specific expertise, the necessity of which is determined by the specificity of the objects, is of particular importance in the investigation of offenses characterized by forgery of plastic cards. Supplementing the methodology for plastic card research using specific expertise should be used in combination with possibilities of traditional forensic examination. The article covers questioned document examination that is most often used in proceedings in which research objects are forged plastic cards. Emphasis is made on the characteristics of plastic cards and their protection against forgery as the main research objects. It is emphasized that means of card security, often referred to as security elements, include the following: graphic record, embossing, barcodes, magnetic stripe coding, chip, and laser recording. The analysis of forensic examinations conducted during the pre-trial proceedings concerning forged vehicle registration certificates and driver’s licenses is provided. The article details peculiarities of forgery production and stresses issues that cannot be solved with the help of traditional forensic examination methods. The application of specific expertise is possible within advisory activities concerning identification of potential violations involving forged plastic cards. The author has concluded that there is a need to conduct multidisciplinary expert research on plastic cards. This research would determine: whether the card submitted for study has been forged and how the forgery has been executed; whether the card has been produced by the issuing enterprise; and whether the examined card has been made from the same materials and on the same technological equipment as other cards from the same batch, etc. Diverse methods of committing violations using plastic cards, use of modern technical means by the offenders, and the insufficient informational support of investigators and forensic experts during a pre-trial proceeding lead to low effectiveness in revealing such types of offences.